2012
DOI: 10.1002/star.201200081
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted acetylation of mung bean starch and the catalytic activity of potassium carbonate in free‐solvent reaction

Abstract: Mung bean starch acetate has been successfully produced with transesterification reaction of the starch under microwave assistance using vinyl acetate (VAC) as esterifying agent and potassium carbonate (K2CO3) as a catalyst. Various concentration of potassium carbonate (0–0.117 mmoleq/AGU) was resulted in starch acetate with increased mood of the degree of substitution (DS = 0.003–0.27) in a short time. An increase in the degree of substitution, resulting in increase of the peak intensity of ester carbonyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Shi et al [5] concluded that starch esterification with malic acid causes a significant decrease in both its water solubility and swelling power. Changes in these properties are determined by the reagent type and conditions of the modification process [47][48][49][50][51][52][53][54][55][56][57][58][59]. In addition, starches with a low degree of substitution are usually characterized by a higher solubility in water and a higher swelling power when compared to starch with a high substitution degree [60][61][62][63][64][65].…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al [5] concluded that starch esterification with malic acid causes a significant decrease in both its water solubility and swelling power. Changes in these properties are determined by the reagent type and conditions of the modification process [47][48][49][50][51][52][53][54][55][56][57][58][59]. In addition, starches with a low degree of substitution are usually characterized by a higher solubility in water and a higher swelling power when compared to starch with a high substitution degree [60][61][62][63][64][65].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, reaction time can be significantly reduced by microwave radiation. The synthesis of acetylated starch by traditional methods usually requires several hours; however, the acetylation reaction by the microwave‐assisted method can be completed in a few minutes . Because acetylated starch products synthesized by traditional methods tend to have very high viscosity, which can negatively affect sizing performance, a hydrolytic reaction is often required prior to acetylation .…”
Section: Introductionmentioning
confidence: 99%
“…Considerably fewer literature data concern changes in amylose content of starch subjected to the crosslinking process. Jane et al [1992] report that the crosslinking of native starch does not Bushra et al, 2013]. The monoesters with a low degree of substitution (the maximum percentage of substitution with acetic acid residues reaches 2.5%; percentage of substitution with adipic acid residues reaches 0.135%) applied in the food industry are usually characterized by increasing solubility and swelling power along with an increasing esterifi cation degree.…”
Section: Resultsmentioning
confidence: 99%